Implementing the Trade Facilitation Agreement: From vision to reality - Nora Neufeld (World Trade Organization (WTO), 2016)
After a decade of negotiations and additional preparatory work, the WTO Trade Facilitation Agreement (TFA) is poised to enter into force. It promises to streamline and substantially prune the red tape that all too often slows and impedes international commerce - thereby significantly reducing both cost and time needed to do business across borders. The paper chronicles the path from the conclusion of the talks at the 2013 Bali Ministerial Conference to the present day as we prepare for the Agreement to take effect. It reviews the state of the ratification process, analyses implementation schedules and outlines work still to be done. The study shows that the emerging application of the TFA, like its negotiation, has once again confounded the sceptics - who first doubted that a TF Agreement would see the light of day and then questioned if it would ever be put into practice. While plenty remains to be done to implement the TFA across the full WTO membership, its entry into force is set to happen - a valedictory moment.
Keywords: 330; Trade Facilitation Agreement; TFA; trade facilitation negotiations; category A; B and C notifications; ratification; entry into force; WTO Agreement; amendment protocol; Bali Ministerial Conference